2010
DOI: 10.1124/jpet.110.167650
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Receptor is a Primary Regulator of Target-Mediated Drug Disposition of Interferon-β in Mice

Abstract: The purpose of this study is to evaluate the primary mechanism through which interferon (IFN)-␤ exhibits target-mediated drug disposition (TMDD) and whether the theoretical assumptions of TMDD models are consistent with experimental pharmacokinetic (PK) data. Recombinant murine IFN-␤ was administered as an intravenous injection at two dose levels (0.5 and 1 million IU/kg) to male wild-type (WT) and type-I IFN-␣/␤ receptor subunit (IFNAR-1) knockout (KO) mice (A129S7/SvEvBrd strain). Sampling was conducted at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Mager and Jusko [7] were the first to propose a general PK model for drugs exhibiting TMDD, which has provided the basis for extensive further studies and development (see for example [8,9,10,11,5]). Experimental confirmation of TMDD model predictions was provided in a recent elegant study by Abraham et al [12], who showed marked differences in interferon (INF)-β PK in wild-type and type-1 INF α/β receptor knockout mice.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Mager and Jusko [7] were the first to propose a general PK model for drugs exhibiting TMDD, which has provided the basis for extensive further studies and development (see for example [8,9,10,11,5]). Experimental confirmation of TMDD model predictions was provided in a recent elegant study by Abraham et al [12], who showed marked differences in interferon (INF)-β PK in wild-type and type-1 INF α/β receptor knockout mice.…”
Section: Introductionmentioning
confidence: 90%
“…During this initial fast phase, u and v remain approximately constant while y quickly decreases to its minimum and so we can approximate this minimum by setting u = u(0) = 1 and v = v(0) = 1. Substituting these values into (12) and ignoring the higher order terms gives an approximation to the minimum value of y as…”
Section: Approximation Of the Drug Potency -Methodsmentioning
confidence: 99%
“…IFN-b remained below ELISA's detection levels in sera from ZH548-infected MBT/Pas and BALB/cByJ mice. This may be due to the fact that, at low concentrations, IFN-b rapidly binds to its receptor, and serum concentrations of the free IFN-b decrease rapidly (29). In addition, we tested the susceptibility of MBT/Pas mice to other viruses.…”
Section: Increased Susceptibility Of Mbt/pas Mice To Rvfv Infectionmentioning
confidence: 99%
“…Although initially generated based on the behavior observed in a number of small‐molecule compounds mentioned above, the concept of TMDD is more widely recognized and well appreciated in peptide‐ and protein‐based pharmaceuticals (ie, large‐molecule compounds) due to the high prevalence of TMDD in this type of drug. Numerous large‐molecule compounds, including interferon‐β1a, erythropoietin, thrombopoietin, M‐CSF, pegfilgastim, and various monoclonal antibodies, have been reported to exhibit nonlinear pharmacokinetics imparted by TMDD . Different from large‐molecule compounds, which usually have high‐affinity binding to their pharmacological targets with minimal nonspecific tissue binding, the saturable target binding of small‐molecule compounds is often masked by the binding to those nonspecific sites (tissue and/or plasma) whose capacity is usually larger.…”
mentioning
confidence: 99%